1988
DOI: 10.1007/bf00445922
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of vitamin K1 and PIVKA-II in bottle-fed and breast-fed infants with and without vitamin K prophylaxis at birth

Abstract: Plasma vitamin K1 and proteins induced by vitamin K absence (PIVKA) were assayed simultaneously 1-4 days and 29-35 days after delivery in three groups of infants: breast-fed not receiving vitamin K at birth (n = 12), bottle-fed without vitamin K administration at birth (n = 7) and breast-fed receiving 1 mg vitamin K1 administered by intramuscular injection at birth (n = 13). The bottle-fed infants had a significantly higher vitamin K1 plasma level than breast-fed infants who did not receive vitamin K1 at birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 14 publications
5
25
0
Order By: Relevance
“…In one study of 51 newborn blood samples from Japan, using the same assay as in our study, 21.5% exhibited PIVKA-I1 ranging from 0.13 to 1 AU/ml (13). In another study from the Netherlands, again using the same assay, PIVKA-I1 was detected in 31% five of 16 cordblood samples); the range was 0.22-3.86 AU/ml (23). In our study, PIVKA-I1 was detected in 54% of control newborn (six of 11 samples); range, 0.18-4.43.…”
Section: Pivka Levels In Control Neonatessupporting
confidence: 73%
“…In one study of 51 newborn blood samples from Japan, using the same assay as in our study, 21.5% exhibited PIVKA-I1 ranging from 0.13 to 1 AU/ml (13). In another study from the Netherlands, again using the same assay, PIVKA-I1 was detected in 31% five of 16 cordblood samples); the range was 0.22-3.86 AU/ml (23). In our study, PIVKA-I1 was detected in 54% of control newborn (six of 11 samples); range, 0.18-4.43.…”
Section: Pivka Levels In Control Neonatessupporting
confidence: 73%
“…McNinch et al (10) detected a peak level of 1781 ng/mL after 12 h. This shows that the blood lymphocytes in the vitamin K group certainly have been exposed to extremely high levels of vitamin K before sampling. Previous studies have shown that the plasma level declines rapidly ( 12).…”
Section: Discussionmentioning
confidence: 94%
“…The hepatic synthesis of these vitamin K-dependent factors differs from other coagulation factors in that their functional activity is also dependent on the integrity of the microsomal g-glutamyl carboxylation system, which converts the inactive protein precursors to their active zymogens, with a reduced ratio of functional to antigenic levels of prothrombin being a hallmark of an impaired carboxylation resulting in the hepatic secretion of non-functional PIVKA-II [22,23]. In ALF, it has been commonly assumed that the reduced levels of prothrombin (and other vitamin K-dependent proteins) are due to impaired hepatic protein synthesis [22].…”
Section: Discussionmentioning
confidence: 99%